Disability in Islam: a Sufi perspective - Masotta, Kabira (Journal of disability & religion, 2021)
In Islam, the issue of disability and vulnerability has only been addressed at the sociological or theological-legal level. The studies mainly highlighted the societal nature of disability and the legal issues faced by vulnerable groups, with theological issues thus remaining intimately linked to legal issues. Vulnerability is a positive notion present in the Qur’an and hadith, generating legislation for deficient individuals that insist on the duties that fall to the society. The objective of this communication will thus be to examine precisely the possibility based on the spiritual dimension of making a theology of vulnerability in Islam. Sufism in particular appears to be a fundamental reading key and remains a broad field of investigation to be explored in the investigation of the question. Sufism places the vulnerability of human beings at the heart of their spiritual journey since it participates in their ontological condition as servants, the only guarantee of the emergence of God’s power and presence among us. The interest will therefore be to understand to what extent the teachings of Sufism can offer a contribution for disability discourse.